2016
DOI: 10.35448/jrat.v9i1.4290
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pertumbuhan Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Interverning

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh Pertumbuhan dan Profitabilitas terhadap Nilai Perusahaan dengan menggunakan Struktur Modal sebagai Interverning Variable. Penelitian ini menggunakan laporan keuangan dari data comapany Wholesale dan Retail yang terdaftar di Bursa Efek Indonesia pada periode 2010-2014, menggunakan 8 sampel perusahaan. Dengan hasil menunjukkan bahwa, Pertumbuhan Perusahaan (X1) memiliki nilai Perusahaan positif dan signifikan (Y) diperoleh dari, thitung> ttabel (1,797> 1,688) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…The results of testing the hypothesis using the help of EViews 10, the result is that information asymmetry does not affect firm value so it can be concluded that H1 is rejected. This means that the firm value of the property and real estate companies listed on the IDX is not affected by information asymmetry, or in other words, the main factor that creates property and real estate firm value is not due to information asymmetry but other factors (Adri & Anisma, 2015;Aeni & Asyik, 2019;Amelia & Khaerunnisa, 2016). This information asymmetry occurs due to differences in information that is known by management as the party implementing the business with investors and other stakeholders as owners of the company on the basis of the capital invested in the company.…”
Section: Resultsmentioning
confidence: 99%
“…The results of testing the hypothesis using the help of EViews 10, the result is that information asymmetry does not affect firm value so it can be concluded that H1 is rejected. This means that the firm value of the property and real estate companies listed on the IDX is not affected by information asymmetry, or in other words, the main factor that creates property and real estate firm value is not due to information asymmetry but other factors (Adri & Anisma, 2015;Aeni & Asyik, 2019;Amelia & Khaerunnisa, 2016). This information asymmetry occurs due to differences in information that is known by management as the party implementing the business with investors and other stakeholders as owners of the company on the basis of the capital invested in the company.…”
Section: Resultsmentioning
confidence: 99%
“…Hermuningsih, (2012); Anjarwati, Chabachib & Demi (2017); and Musabbihan & Purnawati (2018) declare that the capital structure can intervene the influence of profitability towards the company's value. On the contrary, Musabbihan & Purnawati (2018), Amelia & Khaerunnisa (2016), and Rubiyani & Yuniati (2016) in their research claim that the capital structure cannot intervene the influence of profitability towards the company's value. The capital structure is a funding policy between debt and equity to optimize the firm's value.…”
Section: Introductionmentioning
confidence: 91%
“…Capital structure is a combination of debt and equity that results in a company's long-term funding structure (Amelia & Khaerunnisa, 2016). An optimum capital structure means that a company maximizes the mixture of debt and equity to obtain the highest firm's value.…”
Section: Capital Structurementioning
confidence: 99%
“…Pertumbuhan perusahaan yang positif mengindikasikan bahwa perusahaan tersebut menghasilkan laba yang meningkat seiring berjalannya waktu (Ramdhonah et al, 2019). Peningkatan pertumbuhan perusahaan memberikan indikasi positif terhadap potensi peningkatan profitabilitas sehingga dapat memberikan sinyal baik kepada para investor (Melinia & Priyadi, 2021).…”
Section: Pengaruh Pertumbuhan Perusahaan Terhadap Profitabilitasunclassified
“…Terdapat perbedaan hasil penelitian mengenai pengaruh pertumbuhan perusahaan terhadap profitabilitas. Penelitian yang dilakukan oleh Hama & Santosa (2018), Tondok et al, (2019), Novyanny & Turangan (2019), Putri & Rahyuda (2020), Melinia & Priyadi (2021) dan Yudha et al, (2022) menunjukkan bahwa pertumbuhan perusahaan berpengaruh positif dan signifikan terhadap profitabilitas. Namun hasil penelitian yang berbeda diperoleh dari penelitian Amelia & Anhar (2019), Muliana & Ikhsani (2019) dan Suzulia et al, (2020) yang menunjukkan bahwa pertumbuhan perusahaan berpengaruh negatif dan tidak signifikan terhadap profitabilitas.…”
unclassified